2018
DOI: 10.14735/amko2018260
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of OIP5-AS1 in Non-Small Cell Lung Cancer

Abstract: Background: Lung cancer as the most fatal cancer of men has prompted researchers to find bio markers for early detection and prognosis. Among the possible bio markers are a group of non-coding transcripts with sizes more than 200 nucleotides called long non-coding RNAs (lncRNAs). Aims: In the present study, we evaluated the expression levels of the lncRNA OIP5 antisense RNA 1 (OIP5-AS1) in 32 non-small cell lung cancer (NSCLC) samples compared with their corresponding adjacent non-cancerous tissue (ANCTs) by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Opa-interacting protein 5 antisense transcript 1 (OIP5-AS1) is a long intergenic noncoding RNA located in human chromosome at 15q15.1 and transcribed in the antisense of OIP5 gene (14)(15)(16). Also, OIP5-AS1 has been known to regulate the progression of multiple malignancies, such as breast cancer (17,18), malignant melanoma (19), osteosarcoma (20,21), lung adenocarcinoma (22)(23)(24), bladder cancer (25), and colorectal cancer (26). However, the role of OIP5-AS1 in CC is still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Opa-interacting protein 5 antisense transcript 1 (OIP5-AS1) is a long intergenic noncoding RNA located in human chromosome at 15q15.1 and transcribed in the antisense of OIP5 gene (14)(15)(16). Also, OIP5-AS1 has been known to regulate the progression of multiple malignancies, such as breast cancer (17,18), malignant melanoma (19), osteosarcoma (20,21), lung adenocarcinoma (22)(23)(24), bladder cancer (25), and colorectal cancer (26). However, the role of OIP5-AS1 in CC is still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, our study did not verify the overexpression of LINC01433 in NSCLC Iranian patients despite the reported oncogenic role of this lncRNA. In our recent study of assessment of OIP5-AS1 expression in lung cancer tissues, we also reported down-regulation of this lncRNA [5], despite the reported oncogenic role of OIP5--AS1 in other studies [10]. Such results necessitate assessment of expression profile of genes in each ethnic group and potentiate the contribution of genetic/ environmental factors in regulation of gene expression in tumoral tissues.…”
Section: Expression Assaymentioning
confidence: 76%
“…Their participations in various cellular processes, for instance proliferation, metastasis and stem cell renewal, has potentiated them as dia gnostic biomarkers in NSCLC [4]. We have recently reported dysregulation of some lncRNAs in NSCLC tissues of Iranian patients [5,6]. A previous study, which aimed at identification of lung-cancer-related lncRNAs, has detected alterations in lncRNA profile in the human bronchial epithelial cell line after transformation of cells by antibenzo(a) pyrene-7,8-diol-9,10-epoxide.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, OIP5-AS1 functions as a ceRNA for miR-195-5p to up regulate NOB1 in human hemangioma endothelial cells [149]. It has been observed that there were significant decreased levels of OIP5-AS among a sub population of Iranian non-small cell lung cancer (NSCLC) samples compared with their corresponding normal margins [150]. In contrast with the results among Iranian NSCLC cases, it has been observed that there was OPI5-AS1 up regulation in a sample of Chinese lung adenocarcinoma tissues.…”
Section: Leukemia and Lung Cancermentioning
confidence: 99%